Tvivl og tolerance (Vol. 15):Et skrift om Pierre Bayle, en milepæl og et paradoks i oplysningens historie - John Pedersen (Romanske Skrifter, 2006)
The philosopher Pierre Bayle (1647-1706) is one of the most enigmatic figures in the history of the European Enlightenment. He was persecuted by the Catholics for his Calvinist beliefs. He was seen as a heretic by his co-religionists because of the doubt that was an essential part of his view of life. He became an icon for many of the Enlightenment's most prominent figures because of his inveterate defence of religious tolerance. He is widely unknown in today's Denmark. You could call him a figure of Christian Enlightenment, a tolerant warrior, born in a time of war, where Catholic France carried through a bloody showdown with its Protestant population. He was an exceptionally gifted thinker who spoke on behalf of toleration, thus becoming an emblematic figure for Enlightenment thinkers as Montesquieu and Voltaire. Religious fanaticism was Bayle's primary enemy; the contending parties should be brought to an awareness of their lack of tolerance. His life and battles seems like a prelude to the Enlightenment. Because of this Bayle and his writings are important elements in a still on-going battle: the battle between fanaticism and tolerance.